PETROGENESIS OF TERTIARY MAFIC ALKALINE MAGMAS IN THE HOCHEIFEL, GERMANY - Jung C.; Jung S.; Hoffer E.; Berndt Ja. (My University, 2006)
Primitive nephelinites and basanites from the Tertiary Hocheifel area of Germany (part of the Central European Volcanic Province; CEVP) have high Mg-number (>0·64), high Cr and Ni contents and strong light rare earth element enrichment but systematic depletion in Rb, K and Ba relative to trace elements of similar compatibility in anhydrous mantle. Alkali basalts and more differentiated magmatic rocks have lower Mg-number and lower abundances of Ni and Cr, and have undergone fractionation of mainly olivine, clinopyroxene, Fe–Ti oxide, amphibole and plagioclase. Some nephelinites and basanites approach the Sr–Nd–Pb isotope compositions inferred for the EAR (European Asthenospheric Reservoir) component. The Nd–Sr–Pb isotope composition of the differentiated rocks indicates that assimilation of lower crustal material has modified the composition of the primary mantle-derived magmas. Rare earth element melting models can explain the petrogenesis of the most primitive mafic magmatic rocks in terms of mixing of melt fractions from an amphibole-bearing garnet peridotite source with melt fractions from an amphibole-bearing spinel peridotite source, both sources containing residual amphibole. It is inferred that amphibole was precipitated in the asthenospheric mantle beneath the Hocheifel, close to the garnet peridotite–spinel peridotite boundary, by metasomatic fluids or melts from a rising mantle diapir or plume. Melt generation with amphibole present suggests relatively low mantle potential temperatures (<1200°C); thus the mantle plume is not thermally anomalous. A comparison of recently published Ar/Ar ages for Hocheifel basanites with the geochemical and isotopic composition of samples from this study collected at the same sample sites indicates that eruption of earlier lavas with an EM signature was followed by the eruption of later lavas derived from a source with EAR or HIMU characteristics, suggesting a contribution from the advancing plume. Thus, the Hocheifel area represents an analogue for magmatism during continental rift initiation, during which interaction of a mantle plume with the overlying lithosphere may have led to the generation of partial melts from both the lower lithosphere and the asthenosphere.
Keywords: alkali basalts; continental volcanism; crustal contamination; partial melting; Eifel; Germany